Principles of Treatment in Osteoarthritis - Pınar Özgürsoy (Archives of Rheumatology, 2006)
Osteoarthritis (OA) is the most prevalent chronic joint disorder worldwide and is associated with significant pain and disability. The effective treatment of osteoarthritis is complex and subject to many treatment- and patient-related variables. The treatment includes nonpharmacologic modes of therapy as well as pharmacologic agents. In this review the treatment approaches will be discussed. (Rheumatism 2006; 21: 67-72)